Indirect insulin resistance detection: Current clinical trends and laboratory limitations - Placzkowska, Sylwia; Pawlik-Sobecka, Lilla; Kokot, Izabela; Piwowar, Agnieszka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
There is a steady increase in the number of overweight and obese people worldwide and increasingly, younger people. Excess adipose tissue impairs the action of insulin, leading to insulin resistance (IR). Tissue IR is a major factor in relation to cardiovascular disease, metabolic syndrome and diabetes. Thus, it is important to recognize at the pre-disease stage with the possibility of therapeutic intervention. IR is assessed using indicators of epidemiological significance, most often calculated from fasting and postprandial glucose and insulin values, so-called indirect indicators of insulin resistance. The most commonly used parameter is the Homeostatic Model Assessment (HOMA). Although the Quantitative Insulin Sensitivity Check Index (QUICKI), Matsuda Index and the Insulin Secretion-Sensitivity Index-2 (ISSI-2) are also used, the values of these indices established for IR vary for different age, sex, populations and ethnic groups. Thus, appropriate reference values of indirect indices should be determined for such groups, and when this is precluded, data from published studies carried out on the most ethnically, socio-economically and age-matched populations should be applied.
Keywords: referenční hodnoty; decision limit; Humans; Glycemic Index; Insulin Resistance; Insulin Secretion; Female; lidé; Blood Glucose; Glucose Tolerance Test; glukózový toleranční test; ženské pohlaví; homeostáza; Male; inzulinová rezistence; insulin resistance; krevní glukóza; Homeostasis; Reference Values; reference interval; sekrece inzulinu; mužské pohlaví; glykemický index